University-industry collaboration and research product commercialization : a case study in selected higher learning institution - Nurul 'Atiqah Yahaya (2018)
This study intends to address the failure of synergy between universities and industries that leads to ineffective research product commercialization. The factors of collaboration issues are universities and industries have low engagement with each other. Besides, research product commercialization among academicians in Malaysia is not encouraging and less progress. Other several issues including misunderstanding of roles in collaboration, university researchers are lack of entrepreneurial skills, lack of research skills, researchers are battling with workload issues, university produce unsatisfactory of research product commercialization and researchers attitude towards learning and doing research. This study utilizes the qualitative research approach using in-depth interview conducted through face to-face. Seven respondents were selected consisting of those who are directly involved and has knowledge on issues regarding university and industry collaboration, as well as research product commercialization. The findings of the study found that researcher's creativity to develop research product, market survey, product marketability, support structure, recognition and respect for researchers and products, plagiarism, attitude and mindset as contributing factors that affect university and industry collaboration and research product commercialization. This study contributes effective university and industry collaboration and research product commercialization. For future research, researchers may adopt the quantitative research approach to identify factors affecting university and industry collaboration and research product commercialization in other universities. Perhaps, researcher will identify different issues and findings due to the phenomena of collaboration and research product commercialization within the university is not the same.